2006
DOI: 10.1098/rspb.2006.0214
|View full text |Cite
|
Sign up to set email alerts
|

Male phenotypic quality influences offspring sex ratio in a polygynous ungulate

Abstract: Evolutionary models of sex ratio adjustment applied to mammals have ignored that females may gain indirect genetic benefits from their mates. The differential allocation hypothesis (DAH) predicts that females bias the sex ratio of their offspring towards (more costly) males when breeding with an attractive male. We manipulated the number of available males during rut in a polygynous ungulate species, the reindeer (Rangifer tarandus), and found that a doubling of average male mass (and thus male attractiveness)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 52 publications
4
36
0
1
Order By: Relevance
“…However, in our study sex ratio only was affected by age class, while no other variable in hinds, such as body condition or weight, had any effect on it. Røed et al (2007) reported that females produce more sons when mating with an attractive male. Nevertheless, in our experiment male and female were housed separately during the non-mating season, when one female was near to be heat in rut season, then one male was introduced into the female's enclosure, and then taken back to its original enclosure after the female ended estrus.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study sex ratio only was affected by age class, while no other variable in hinds, such as body condition or weight, had any effect on it. Røed et al (2007) reported that females produce more sons when mating with an attractive male. Nevertheless, in our experiment male and female were housed separately during the non-mating season, when one female was near to be heat in rut season, then one male was introduced into the female's enclosure, and then taken back to its original enclosure after the female ended estrus.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental reindeer herd at the Station amounts to around hundred winter animals which are free ranging within large seasonal grazing enclosures (altogether~40 km 2 ) (Holand et al 2006;Røed et al 2007;Mysterud et al 2009). Birch (Betula spp.)…”
Section: Study Areamentioning
confidence: 99%
“…There is evidence that offspring sex ratios may be adjusted in relation to the attractiveness of the father (Ellegren et al 1996). Similarly, in mammals offspring sex ratio is influenced by male body mass (Røed et al 2006). However, it is widely assumed that such manipulation is under female control.…”
Section: Male Fertility and Offspring Sex Ratiomentioning
confidence: 99%